2009
DOI: 10.1007/s10433-009-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component health promotion and disease prevention for community-dwelling frail elderly persons: a systematic review

Abstract: The objective was to investigate definitions of frailty used in studies of multi-component health promotion and disease-preventive (HPDP) intervention programmes for community-dwelling frail elderly persons and to review the content, organisation and effects of HPDP interventions. A systematic review of 19 articles was made, and the International Classification of Functioning, Disability and Health (ICF) was used as a structural framework for the analysis. The result shows that a consensus was reached on inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 55 publications
0
51
0
3
Order By: Relevance
“…The fact that the senior meetings in the current study were multiprofessional and had a participatory and client‐centered approach (i.e., the discussions focused on individual needs) might be part of the explanation. This is described in two reviews of interventions for frail older adults that point to these factors as promising features in health promotion for older adults . The positive outcome of the current study might also be because the senior meetings were group based, which could be a favorable pedagogical form for this population and for targeting ADLs .…”
Section: Discussionmentioning
confidence: 85%
“…The fact that the senior meetings in the current study were multiprofessional and had a participatory and client‐centered approach (i.e., the discussions focused on individual needs) might be part of the explanation. This is described in two reviews of interventions for frail older adults that point to these factors as promising features in health promotion for older adults . The positive outcome of the current study might also be because the senior meetings were group based, which could be a favorable pedagogical form for this population and for targeting ADLs .…”
Section: Discussionmentioning
confidence: 85%
“…The findings show that the participants experienced that they had received a holistic picture of the topics discussed with the different professionals at the meetings, and that it contributed to their learning a preventive approach. A recent literature review shows that a multi-dimensional program requires a diversity of professionals in order to be effective [46]. The authors concluded that the different professionals probably had their own way of "framing the problem", which means that a multi-professional approach is desirable in view of the complexity of health promotion and disease prevention for elderly persons.…”
Section: Discussionmentioning
confidence: 96%
“…Common outcome measures on trials of case management interventions have captured clinical outcomes such as self‐rated health, depression, quality of life, cognitive functioning, medical conditions, and IADL and ADL ability, or healthcare consumption outcomes such as hospital admissions and costs (Rahm Hallberg & Kristensson , Eklund & Wilhelmson , Gustavsson et al . , You et al . ).…”
Section: Introductionmentioning
confidence: 99%